Fitoremediasi Logam Berat Timbal (Pb) oleh Tanaman Kiapu (Pistia stratiotes) Berdasarkan Analisis Mass Balance - Tarigan-Sibero, Nita Hayani Br.; Wijayanti, Ni Putu Putri; Perwira, Ima Yudha (Current Trends in Aquatic Science, 2019)
Abstract This study was aimed to investigate the phytoremediation capacity and mechanism of Pb by Kiapu plants ( Pistia stratiotes ) based on the mass balance analysis. This study used 2 treatments, Pb exposure at 10 and 20 ppm. The phytoremediation capacity of Kiapu plants was represented by the absorption/adsorption rate of Pb by the plants during 20 days of cultivation. The mechanism of Pb phytoremediation by Kiapu plants was estimated in mass balance analysis (the mass of Pb in leaves and roots). The value of Pb mass accumulation (in leaves and roots) was used as the basis of phytoremediation mechanism determination. The results showed that Kiapu plants could absorp/adsorp Pb from the water up to 0,71%  in leaves and 0,79% in roots out of 50,5 mg in the 10 ppm treatment and that of  0,50%  in leaves and 0,52% in roots  out of 100,25 mg in the 20 ppm treatment. These result showed that the highest absorption/adsorption was in the root of the plants indicating a rhyzofiltration mechanism during the phytoremediation process. The water quality was not effected by phytoremediation using Kiapu plants. Keywords: Phytoremediation, capacity, mechanism, Kiapu (Pistia stratiotes), mass balance